Interaction products of cytotoxic Cu(I) complexes with different solvent mixtures: an electrospray ionization mass spectrometry and density functional theory study. (9th December 2016) - Tisato, Francesco; Forrer, Daniel; Tamburini, Sergio; Vittadini, Andrea; Traldi, Pietro; Porchia, Marina
Abstract : Rationale: [Cu(P)4 ][BF4 ]‐type complexes (P = tertiary phosphine) have shown significant antitumor activity. This biological property appears to be activated via formation of coordinative unsaturated [Cu(P)n ] + species ( n < 4), that may interact with various molecules starting from the solvent(s) in which they are dissolved. Aim of our study was to investigate the interaction of these species with different solvent mixtures. Methods: The interaction has been investigated by electrospray ionization mass spectrometry, and the interaction products have been characterized by multiple collisional experiments, using an ion trap mass instrument. Density functional theory (DFT) calculation studies, using a meta‐hybrid exchange correlation (xc) functional and an implicit solvent model, were employed to investigate the equilibrium distribution of species in solution. Results: Depending on the nature of the solvent mixture and coordinated phosphine, three [Cu(P)4 ][BF4 ]‐type complexes undergo dissociation with formation of [Cu(P)2 ] +, [Cu(P)(solv)] + and [Cu(solv)2 ] + species (solv = solvent). Preferred collisional‐induced fragmentation pathways provide qualitative information on the selectivity of [Cu(P)n ] + for specific solvents and donor atoms. Formation free energies and equilibrium constants pertaining to [Cu I (PTA)n ] +, [Cu I/II (solv)n ] m+ ( n ≤ 4; m = 1, 2) and [Cu I (PTA)2‐k (sol)k ] + (k = 1, 2) provide a comprehensive picture of equilibria in solution. Conclusions: Dimethyl sulfoxide (DMSO) and acetonitrile (MeCN) strongly affect [Cu(P)n ] + assemblies producing mixed‐ligand [Cu(P)(DMSO)] + and [Cu(P)(MeCN)] + species. Excess of both DMSO and MeCN solvents are able to fully displace coordinated phosphines giving [Cu(solv)2 ] + ‐type adducts. The presence of phosphines in the native complex is mandatory to retain the reduced oxidation state of copper. Instead, the more labile [Cu I (MeCN)4 ] + complex dissolved in DMSO and MeCN displays a combination of Cu(I) and Cu(II) adducts. Copyright © 2016 John Wiley & Sons, Ltd.